Historia 4º Segundo ciclo E.S.O. - CALVO, Isabel; HIDALGO, Antonio; IZQUIERDO, Remedios; LUCIA, Pilar (RIALLA, OCTAEDRO, 1999)
Contenido : DIRECTORES: MADALENA CALVO, José Ignacio; LLOPIS, Enric Pedro; MAESTRO GONZALEZ, Pilar